Estimation of male stature by ulnar length in Madhya Pradesh region by using linear regression analysis - Sandeep K Marskole; Deepak Sharma; Vandana A Sharma; Sonia S Baweja (International Journal of Medical Research and Review, 2017)
Introduction: Establishment of reliable formula for stature estimation from fragments of bones especially in forensic examination is important for individual identification. Sexual differences in height and of long bones exist so there is need for studies emphasizing quantitative standards of sexual dimorphism in different populations. Limited availability of gender specific studies of stature estimation by using individual bones provide data for forensic identification that led me to study ulna bone to establish a linear regression equation for stature estimation in living adult males of age group 18-26 yrs in Madhya Pradesh region.Material & Methods: Cross sectional study was conducted in Department of Anatomy, Gandhi Medical College, Bhopal (M.P.) on 238 males by using anthropometer and spreading caliper and statistically analyzed. Ulna length were measured independently on right and left sides of each subject with the help of spreading caliper from the tip of olecranon process to the tip of styloid process and vertex to heel height was measured in the standing erect posture with subject looking forward straight to the horizon.Results: Value of correlation coefficient(r) of right ulna with stature was found to be 0.995 and left ulna with stature was 0.997. Regression equations and graphs interpret the height from the ulnar length in males.Conclusion: The regression formula derived will be useful for anatomists, clinician, anthropologists and forensic experts for estimation of the individual stature in Madhya Pradesh region for establishing identity.